2020
DOI: 10.1186/s13287-020-01710-x
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cell-derived endothelial cells increase capillary density and accelerate angiogenesis in mouse hindlimb ischemia model

Abstract: Background: Mesenchymal stem cells (MSCs) can improve limb perfusion and increase vessel density in a murine model of hindlimb ischemia. But low engraftment rate of those cells limited their therapeutic effect. Endothelial cells (ECs) play an important role in neovascularization. And MSCs can differentiate into ECs in vitro. The aim of this study is to investigate if EC differentiation of MSCs in vitro before transplantation is effective in improving therapeutic outcomes in the treatment of ischemic disease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Various studies have demonstrated the role of MSCs in angiogenesis and arteriogenesis, useful in improving coronary heart disease, skin wound healing, and hindlimb ischemia [ 56 58 ]. Acting as intermediary of angiogenesis, MSCs release various growth factors, such as vascular endothelial growth factor (VEGF), fibroblast growth factors (FGFs), hepatocyte growth factor (HGF), stromal cell-derived factor 1 (SDF-1), and angiopoietin-1 (ANG-1).…”
Section: Secretome Angiogenic Pro-survival and Tissue Regeneration Propertiesmentioning
confidence: 99%
“…Various studies have demonstrated the role of MSCs in angiogenesis and arteriogenesis, useful in improving coronary heart disease, skin wound healing, and hindlimb ischemia [ 56 58 ]. Acting as intermediary of angiogenesis, MSCs release various growth factors, such as vascular endothelial growth factor (VEGF), fibroblast growth factors (FGFs), hepatocyte growth factor (HGF), stromal cell-derived factor 1 (SDF-1), and angiopoietin-1 (ANG-1).…”
Section: Secretome Angiogenic Pro-survival and Tissue Regeneration Propertiesmentioning
confidence: 99%
“…The endothelial-like cells (ECs) were injected into the paracentral thigh of the gastrocnemius muscle in 3 various places within 1 day after the model surgery. The ECs could increase therapeutic result of angiogenesis and have stronger ability in vascular creation [78].…”
Section: Bone Marrow Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Otherwise, MSCs have been found to promote cardiomyocyte DNA synthesis and proliferation, and signal cardiomyocyte gene upregulation (including VEGF, cyclin A2, and TGF-β2) ( 194 , 233 ). Through their paracrine activity, they also prevent cardiomyocyte cell apoptosis ( 188 , 221 , 234 236 ) with several studies observing a reduced activation of the caspase-3 pathway in cardiomyocytes exposed to either MSC-derived exosomes ( 236 ) or conditioned media ( 237 ).…”
Section: Msc Transplantation Could Attenuate Damage and Facilitate Rementioning
confidence: 99%